2022
DOI: 10.18632/aging.203846
|View full text |Cite
|
Sign up to set email alerts
|

Novel necroptosis-related gene signature for predicting the prognosis of pancreatic adenocarcinoma

Abstract: Pancreatic adenocarcinoma (PAAD) is a deadly digestive system tumor with a poor prognosis. Recently, necroptosis has been considered as a type of inflammatory programmed cell death. However, the expression of necroptosis-related genes (NRGs) in PAAD and their associations with prognosis remain unclear. NRGs' prediction potential in PAAD samples from The TCGA and GEO datasets was investigated. The prediction model was constructed using Lasso regression. Co-expression analysis showed that gene expression was clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
3
40
0
Order By: Relevance
“…Compared with them, our model had outstanding general applicability with high accuracy and stability. As to the miRNA or lncRNA-related signatures 65 , 69 71 , our PAAD-IRGS was more stable and convinced; Compared with multiple-gene signatures 9 , 68 , necroptosis-related gene signature 72 and m6A-related gene signature 73 , 74 , which had been reported, our PAAD-IRGS was new and more versatile with outstanding performance. It can be well applied to prognostic prediction of multiple cancers with different prognostic parameters.…”
Section: Discussionmentioning
confidence: 67%
“…Compared with them, our model had outstanding general applicability with high accuracy and stability. As to the miRNA or lncRNA-related signatures 65 , 69 71 , our PAAD-IRGS was more stable and convinced; Compared with multiple-gene signatures 9 , 68 , necroptosis-related gene signature 72 and m6A-related gene signature 73 , 74 , which had been reported, our PAAD-IRGS was new and more versatile with outstanding performance. It can be well applied to prognostic prediction of multiple cancers with different prognostic parameters.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, its characteristics have been described in a variety of human tumors. Generally, according to different subtypes of necroptosis, the prognosis of patients can be accurately predicted [ 6 , 7 ]. In hepatocellular carcinoma, it has been recognized that necroptosis is a double-edged sword that provides the inflammatory environment required for carcinogenesis, while the immune response is launched to fight against tumors [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, inflammatory responses caused by cytokines released by necrotic cells can promote the development of tumors [ 4 , 5 ]. Recently, a prognosis-related necroptosis gene signature was used to predict the prognosis and describe the immune microenvironment in human tumors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from cellular apoptosis, necroptosis has been recognized as a specially programmed cell death with an essential role in maintaining the stabilization of the internal environment and participating in the pathogenesis of multiple diseases including various infections, tumor formation, and autoimmune diseases ( Schreiber et al, 2017 ; Wang et al, 2019 ; Xia et al, 2020 ). Increasing studies have identified necroptosis-related gene signatures and subtypes to predict the prognosis and therapeutic response of multiple tumors including breast cancer ( Chen W. et al, 2022 ), kidney renal clear cell carcinoma ( Chen W. et al, 2022 ), and pancreatic adenocarcinoma ( Wu et al, 2022 ), but there is no research focusing on the relationships between NRGs and LUAD.…”
Section: Discussionmentioning
confidence: 99%